Optimizing IPAS Learning Outcomes Through Inquiry in Class V SDN 192 Barru - Nursyamsi, Nursyamsi; Kirana, Sashi Zahra; Haslinda, Haslinda (JENTRE, 2025)
The purpose of this study is to increase student learning outcomes in Social Science courses including the food chain by implementing inquiry learning methods with diorama media and snakes and ladders activities in class V SDN 192 Barru. This classroom action research was carried out in two phases, each with four meetings. The research subjects consisted of 13 students. Data collecting methods include observation, testing, and documenting. The results revealed a considerable increase in student learning outcomes, with the average pre-test score rising from 28.61 to 47.77 in cycle I and 74.92 in cycle II. Student engagement also increased, with an average of 2.67 in cycle I and 3.51 in cycle II. The utilisation of diorama media and the snakes and ladders game improved students' engagement and knowledge of the food chain idea. This study concluded that the inquiry learning model, when paired with the appropriate learning medium, can increase student learning results in science disciplines.